Maternal Vaccination With a Monocomponent Pertussis Toxoid Vaccine Is Sufficient to Protect Infants in a Baboon Model of Whooping Cough - Kapil, Parul (J Infect Dis, 2018)
BACKGROUND: Bordetella pertussis is a human pathogen responsible for serious respiratory illness. The disease is most severe in infants too young to be vaccinated with most hospitalizations and deaths occurring within this age group. The Advisory Committee on Immunization Practices recommended immunization of pregnant women to protect infants from birth until their first vaccination at 6–8 weeks of age. We previously demonstrated that maternal vaccination with licensed acellular pertussis vaccines protected newborn baboons from disease. We hypothesized that protection was due to toxin-neutralizing, maternal anti–pertussis toxin antibodies and predicted that maternal vaccination with a pertussis toxoid (PTx)–only vaccine would protect newborns from disease. METHODS: Infant baboons born to unvaccinated mothers or mothers vaccinated with a PTx-only vaccine were challenged with B. pertussis at 5 weeks of age and followed for infection and signs of disease. RESULTS: Although all challenged infants were heavily colonized, the infant baboons born to mothers vaccinated with PTx-only vaccine were free from clinical disease following exposure to B. pertussis. In contrast, disease was observed in infants born to unvaccinated mothers. CONCLUSIONS: Our results demonstrated that maternal vaccination with a PTx-only vaccine is sufficient to protect newborn baboons from disease following exposure to pertussis.